2018
DOI: 10.1075/cal.20.09bat
|View full text |Cite
|
Sign up to set email alerts
|

Evaluative morphology in German, Dutch and Swedish

Abstract: Projektet Det svenska ordförrådets utveckling 1800-2000Projektet Det svenska ordförrådets utveckling 1800-2000 finansieras med generösa bidrag från den kulturvetenskapliga donationen, som administreras av Riksbankens Jubileumsfond. I projektet deltar forskare från fem olika universitets-och högskoleorter och lika många discipliner. Projektet startade den 1 januari 2000. Den gängse förkortningen av projektnamnet är ORDAT (Det svenska ordförrådets utveckling från artonhundra till tjugohundra).Resultat från proje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…Bestaande studies oor affiksoïede is soms taalvergelykend en hoofsaaklik tot die gebruik daarvan in Nederlands, Sweeds en/of Duits beperk (Battefeld, Leuschner en Rawoens 2018;Booij 2010;Booij en Hüning 2014;Ruppenhofer e.a. 2018).…”
Section: Opsommingunclassified
“…Bestaande studies oor affiksoïede is soms taalvergelykend en hoofsaaklik tot die gebruik daarvan in Nederlands, Sweeds en/of Duits beperk (Battefeld, Leuschner en Rawoens 2018;Booij 2010;Booij en Hüning 2014;Ruppenhofer e.a. 2018).…”
Section: Opsommingunclassified
“…Several studies have demonstrated that debonding of intensifying prefixoids is a creative process of lexical innovation in Germanic languages, which may lead to the emergence of new intensifying adverbs or evaluative adjectives (cf. Battefeld et al 2018;Norde and Van Goethem 2014Van Goethem and De Smet 2014;Van Goethem and Hiligsmann 2014;Van Goethem and Hüning 2015). The present paper investigates to which extent the adjectival or adverbial uses of Dutch morphemes with "fake" semantics may be considered instances of debonding.…”
Section: Debondingmentioning
confidence: 99%
“…Earlier research suggests an inverse correlation between semantic coherence and debonding. For instance, Battefeld et al (2018) show that evaluative prefixoids such as German Spitze 'top', Dutch top 'top' or Swedish skit 'shit' debond far more often than compounding elements that have a specific meaning. Similarly, Norde and Van Goethem (2018: 489) found that evaluative prefixoids have a far higher debonding ratio than their equivalents in simile constructions.…”
Section: Semantic Coherence Productivity and Debondingmentioning
confidence: 99%